Mastery of Skills 4.0 Effect on The Readiness of College Students in Facing Revolution of Industry 4.0 - Isna Juwita; Insannul Kamil; Jonrinaldi; Berry Yuliandra; Irsyadul Halim (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
Revolution of industry 4.0 initiated by the German government, starting from the development of individual innovation behavior especially in the fields of robotics, digital technology, and information, has caused distortions to the future skills requirements. Some of the skills needed a lot in the past are now starting to experience a shift towards less needed. Some are even unnecessary because they are replaced by automation and robots. The emergence of several new skills (skills 4.0) that are more dominant is needed to make every interested party to prepare themselves to face the challenges of the revolution of industry 4.0. Students are one of the interested parties who will face the challenges of the revolution of industry 4.0 after they graduates from the formal higher education. This study determines the readiness of students in facing the revolution of industry 4.0, influenced by the mastery of skills 4.0 and individual innovation behavior with their innovation behavior as a mediating variable. Respondents in this study are 233 undergraduate students of the Andalas University. Using a cluster sampling technique, the data is collected using Likert scale based- questionnaire after which calculations are then performed using the Smart-PLS Program software 3.2.8. The results show that skills 4.0 and individual innovation behavior have a positive effect on students' readiness in facing the challenges of the revolution of industry 4.0. It implies that the students need to improve their mastery of skills 4.0 in order to prepare themselves to face the challenges of the revolution of industry 4.0.